Crop response to organic fertilization with supplementary mineral nitrogen - Ciancio,Nathalia Riveros (2014)
Animal manure is applied to the soil as a nutrient source, especially of nitrogen, to plants. However, manure application rates can be reduced with the use of N fertilizer in topdressing. The aim of this study was to evaluate crop responses to different application rates of animal manure sources, used alone and supplemented with mineral N topdressing, in a no-tillage system. The study was carried out from 2005 to 2008 on a Hapludalf soil. The treatments consisted of rates of 10, 20 and 30 m³ ha-1 of pig slurry (PS), and of 1 and 2 t ha-1 of turkey manure (TM), applied alone and supplemented with topdressed N fertilizer (TNF), as well as two controls, mineral fertilization (NPK) and one control without fertilizer application. Grain yield in common bean and maize, and dry matter yield and nutrient accumulation in common bean, maize and black oat crops were evaluated. Nitrogen application in topdressing in maize and common bean, especially when PS was used at rates of 20 and 30 m³ ha-1, and TM, at 2 t ha-1, proved effective in increasing the crop grain yields, showing the viability of the combined use of organic and industrialized mineral sources. Nitrogen accumulation in maize and common bean tissues was the indicator most strongly related to grain yield, in contrast with the apparent nutrient recovery, which was not related to the N, P and K quantities applied in the organic sources. No clear residual effect of N topdressing of maize and common bean was observed on the dry matter yield of black oat grown in succession to the main crops with PS and TM applications.